Competencies of Instructors: Its Correlation to the Factors Affecting the Academic Performance of Students - Sali-Ot, Melrose A. (JPAIR Multidisciplinary Research, 2011)
The study determined the competencies of instructors and its correlation to the factors affecting the academic performance of students in Western Mindanao State University- External Studies Units, Western Mindanao, Philippines. The descriptive research method was employed in the conduct of the study. The respondents were randomly selected with the used of stratified sampling. A questionnaire checklist was the main instrument in collecting data from the respondents. Weighted mean, ranking, and coefficient of correlation by Spearman's formula were used to analyze the data gathered. The instructors are much competent in the five indicators of the teaching competencies. The students' performance was sometimes affected with the predetermined factors. The two groups of respondents have the same responses as to the teachers' competencies and the factors affecting the academic performance. The most prevailing competency was communication with the learners, and the least prevailing is learner reinforcement- involvement. The most prevailing factor was intellectual, and the least prevailing was physical. There was moderate correlation between the competencies of college instructors and the factors affecting the academic performance of students.
Keywords: competencies; instructors; academic performance; factors affecting academic performance